Fertility and Welfare under Demeny Voting - Daryna Grechyna; Rhema Vaithianathan (CESifo GmbH, 2024)
This paper analyzes the welfare implications of children's enfranchisement within a political economy framework that emphasizes the trade-offs in public policy when the electorate includes different age groups. Public spending is financed by tax revenues, meaning that higher spending on child-rearing results in lower pensions, and vice versa. We derive the political equilibrium under Markov strategies and compare welfare across various suffrage schemes and demographic groups. The franchise that maximizes welfare across demographic groups depends on the fertility rate in the economy. Policies chosen when all demographic groups have voting rights are Pareto-improving compared to those chosen under the standard voting rights system, which excludes children from the electorate, when the fertility rate is low, and Pareto-reducing when the fertility rate is high. This result is driven by the surplus or shortage of funds available to finance pensions, depending on the ratio of workers to retirees in the economy. Public investment in child care can change the fertility rate and shift the economy toward a new optimal franchise.
Keywords: H21; J13; D60; D72; 330; demeny voting; children's enfranchisement; fertility; public policy; welfare